PENGARUH SUHU REAKSI, KECEPATAN PENGADUKAN DAN WAKTU REAKSI PADA PEMBUATAN SABUN PADAT DARI MINYAK KELAPA (Cocos nucifera L.) - Rosdanelli Hasibuan, Fransiska Adventi, Rahmad Parsaulian Rtg (Universitas Sumatera Utara, 2019)
Soap is a cleanser made by chemical reactions between sodium hydroxide or potassium hydroxide with fatty acids from vegetable oils or animal fats. Soaps can be made by several methods, namely saponification and neutralization methods, in this study carried out by saponification method. In the saponification method there are several problems namely operating conditions which include reaction temperature, stirring speed and stirring time. Therefore, need to do research to determine the best conditions of saponification reaction, namely reaction speed, operating temperature and reaction time using an impeller type multiple pitch blade turbine with research variables reaction temperature 60 oC, 70 oC, and 80 oC, stirring speed 300 rpm,400 rpm and 500 rpm and reaction time of 45minutes, 60 minutes, and 75 minutes. Saponification reaction is carried out by heating coconut oil and inserting 30% NaOH slowly and then stirring with a multiple pitch blade stirrer. The product will be analyzed by testing alkaline levels, moisture content and pH of the soap. The best operating conditions obtained from this study were at a temperature of 70 oC, reaction time of 60 minutes, stirring speed of 400 rpm with a pH value of 9.4 and an alkaline level of 0.073 and a moisture content of 9.8.